Gender Issues in Barbara Baynton’s Bush Studies - Donny Syofyan (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2021)
This research attempts to address how an Indonesian critic would interpret gender in postcolonial Australian literature in Bush Studies, a short story written by Barbara Baynton. Using French feminism, this writing focuses on how Indonesian critics regard gender issues in postcolonial Australian literature and how Indonesian critics understand it. Furthermore, how Baynton's and Franklin's works challenge the status quo is investigated, and how Indonesian and Australian points of view deal with class and gender concerns when reading these works. For that purpose, close reading becomes a literary research method to understand the very details of the short story. The original contribution that this research would make to this field of expertise will involve exploring how different cultures examine literature and media from cultures not their own, especially as Indonesia and Australia, though both patriarchal, are very different cultures that approach gender differently.